Pengaruh Harga dan Kualitas Produk terhadap Kepuasaan Konsumen di Café Nuiz Kota Palopo - Pagirik, Elvi; Ardhana, Nadya Dwi; Makmur, Hernanda; Nurimansjah, Ris Akril; Suryati (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the effect of price and product quality on consumer satisfaction at Café Nuiz in Palopo City. A quantitative associative approach was employed, with data collected through questionnaires distributed to 30 respondents using an incidental sampling technique. The independent variables in this study are price (X₁) and product quality (X₂), while the dependent variable is consumer satisfaction (Y). Data analysis was performed using multiple linear regression with the assistance of SPSS software. The F-test results indicate that price and product quality simultaneously have a significant effect on consumer satisfaction, with a significance value of 0.016 < 0.05. However, based on the t-test, only product quality has a partially significant effect on consumer satisfaction (significance value 0.012 < 0.05), while the price variable does not show a significant effect (significance value 0.234 > 0.05). The coefficient of determination (R²) is 25.9%, indicating that consumer satisfaction can be explained by the two variables, while the remaining 74.1% is influenced by other factors such as service, café ambiance, and consumers’ personal experiences. These findings highlight the crucial role of product quality in shaping customer satisfaction in the culinary industry.